Rethinking Elective Cataract Surgery Diagnostics, Assessments, and Tools after the COVID-19 Pandemic Experience and Beyond: Insights from the EUROCOVCAT Group - Daniele Tognetto; Antoine P. Brézin; Arthur B. Cummings; Boris E. Malyugin; Ozlem Evren Kemer; Isabel Prieto; Robert Rejdak; Miguel A. Teus; Riikka Törnblom; Mario D. Toro; Alex L. Vinciguerra; Rosa Giglio; et al. (MDPI, 2022)
The progressive deterioration of the visual function in patients on waiting lists for cataract surgery has a negative impact on their quality of life, especially in the elderly population. Patient waiting times for cataract surgeries in many healthcare settings have increased recently due to the prolonged stop or slowdown of elective cataract surgery as a result of coronavirus disease 19 (COVID-19). The aim of this review is to highlight the impact of such a "de-prioritization" of cataract surgery and to summarize some critical issues and useful hints on how to reorganize cataract pathways, with a special focus on perioperative diagnostic tools during the recovery phase and beyond. The experiences of a group of surgeons originating from nine different countries, named the European COVID-19 Cataract Group (EUROCOVCAT), have been combined with the literature and recommendations from scientific ophthalmic societies and healthcare institutions. Key considerations for elective cataract surgery should include the reduction of the number of unnecessary visits and examinations, adoption of precautionary measures, and implementation of telemedicine instruments. New strategies should be adopted to provide an adequate level of assistance and to guarantee safety conditions. Flexibility will be the watchword and regular updates would be necessary following scientific insights and the development of the pandemic.